Application of Structural Equation Modeling (SEM) in Estimating the Contributing Factors to Satisfaction of TASKA Services in East Coast Malaysia - Kharuddin, Azrul Fazwan; Azid, Norazura; Mustafa, Zaida; Ku Ibrahim, Ku Faridah; Kharuddin, Darvinatasya (Asian Journal of Assessment in Teaching and Learning, 2020)
This research shows the application of the Structured Equation Modeling (SEM) to obtain the best model for studying the relationship between the more efficient and accurate against the findings and the interpretation of the variables. The objectives of the study are to assess the reliability of the developed instrument and to test construct validity of the research instruments in estimating the contributing factors to TASKA service satisfaction. The proportionate stratified random sampling method was used to select a total of 61 TASKAs from three states on the east coast of Malaysia consisting of 273 parents and guardians which are currently using the TASKA services. Validity and reliability of the measurement model in the analysis using Structural Equation Modeling (SEM) method. Measurement models were data-based and fit based on the fit index (CMF) χ2 = 3230.541, with degrees of freedom (df) = 902, CMIN / df = 3.582 (≤5.0), CFI & TLI (≤0.9), and RMSEA = 0.070 (≤0.1). Based on the results obtained, all indices meet standardized metric and assessment tools have proven to be a good instrument. The results show that there are 5 factors that influence parents’ satisfaction with the quality of services offered by TASKA. Analysis found that the combination of manage, grow, fees, activity and cost constitutes a strong association to estimate a complete structured equation model while supported by demographic factors such as education level, occupation, location, distance, agency, status and age of children to strengthen the TASKA selection factor. Research shows that this TASKA service model can assist as a guide in improving the existing quality for future improvement. Furthermore, it can be used as a module in providing the best quality of services to the satisfaction of parents and guardians.